A composite of polyethylene terephthalate and sugarcane ash-coated FeSO4 center dot 7H(2)O (PETSCA/Fe) as a low-cost adsorbent material - Isique, William Deodato [UNESP]; Silva, Tatiana Santos da [UNESP]; Matsumoto, Tsunao [UNESP] (Elsevier B.V., 2017)
A new type of composite adsorbent material matrix was prepared containing polyethylene terephthalate and sugarcane ash-coated FeSO4 center dot 7H(2)O particles (PETSCA/Fe). The dependence of the adsorption properties of the composite on the oxidative capacity of PETSCA/Fe coating was investigated by varying the Fe doping concentration. Scanning electron microscopic analysis revealed that PETSCA/Fe particles had an irregular shape and size with roughened surface similar to melanterite. Analysis by energy dispersive spectroscopy identified Fe and Si as well as Na, S, K, Ca and Cu. X-ray diffraction and Fourier transform infrared spectroscopy analysis demonstrated melanterite crystals, which has been widely used for wastewater treatment. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Low-cost adsorbents; Polyethylene terephthalate; Sugarcane ash; Melanterite crystals